2020
DOI: 10.21203/rs.3.rs-63027/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unravelling the modes of transmission of SARS-CoV-2 during a nursing home outbreak: looking beyond the church super-spread event

Abstract: BackgroundAn outbreak of COVID-19 in a nursing home in the Netherlands, following an on-site church service held on March 8, 2020, triggered an investigation to unravel sources and chain(s) of transmission.MethodsEpidemiological data were collected from registries and through a questionnaire among church visitors. Symptomatic residents and healthcare workers (HCWs) were tested for SARS-CoV-2 by RT-PCR and subjected to whole genome sequencing (WGS). Sequences from a selection of people from the same area were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Biased SAR: A treated as only index case 5 7 Biased SAR: B treated as only index case causes the SAR to be biased upwards as the secondary cases from B and perhaps even B themselves will be attributed as secondary cases of A. This is most likely in settings with dynamic populations where the source of infection is unclear (i.e., gyms, bars, nursing homes, or gathering events) and multiple index cases may be infecting people at the same time [61,62]. One example of this bias can be seen in a study from South Korea [58] in which the initial report suggested that the SAR of index cases aged 10-19 years was significantly higher than for index cases aged 20-29, 30-39 and 40-49 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biased SAR: A treated as only index case 5 7 Biased SAR: B treated as only index case causes the SAR to be biased upwards as the secondary cases from B and perhaps even B themselves will be attributed as secondary cases of A. This is most likely in settings with dynamic populations where the source of infection is unclear (i.e., gyms, bars, nursing homes, or gathering events) and multiple index cases may be infecting people at the same time [61,62]. One example of this bias can be seen in a study from South Korea [58] in which the initial report suggested that the SAR of index cases aged 10-19 years was significantly higher than for index cases aged 20-29, 30-39 and 40-49 years.…”
mentioning
confidence: 99%
“…In a re-analysis [63] of this data, the authors removed household members who potentially shared a common source of exposure with the pediatric cases, resulting in a much lower SAR for the 10-19 year group. Another example is a nursing home outbreak investigation from the Netherlands, where a church service was initially thought to be the source of the outbreak; however, genome sequencing showed multiple clusters in the viral genomes, suggesting multiple introductions to the nursing home [62].…”
mentioning
confidence: 99%
“…Previous research has shown that whole genome sequencing can generate evidence for transmission routes that would not have been identified with traditional epidemiological investigations. 17,18…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In addition, during a community-wide outbreak it can be difficult to distinguish residential outbreaks from multiple introductions without sequencing of viruses from cases. 17…”
Section: Introductionmentioning
confidence: 99%
“…When the sequence was known, amplicon-based methods were developed to sequence the new virus in a timely and sensitive manner (( Oude Munnink et al ., 2020a ) “see Relevant Websites section”) Whole genome sequencing was performed at unprecedented scale, with almost 250.000 SARS-CoV-2 whole genome sequences that had been shared on the GISAID platform as of 8 December 2020. The timely release of unpublished genomic information through GISAID was essential for fast track development of diagnostics, vaccines and therapeutics as well as the application of WGS in outbreak investigation and public health control measures ( Oude Munnink et al ., 2020a ; Voeten et al ., 2020 ).…”
Section: Note Added In Proof: December 2020mentioning
confidence: 99%